STUDENTS' FINE MOTOR SKILLS OF PUBLIC ELEMENTARY SCHOOLS LOCATED AT RIO DE JANEIRO (Fiep Bulletin - online, 2011)
Physical education develops critical role in the lives of children and adolescents in and out of school because their activities make possible the generation of a citizen in the fullest development of motor skills, cognitive, affective and social which is extremely important during the pre-school. thus this study has characteristics of type descriptive, comparative field and objectively compare the fine motor skills of children at preschool. the instrument used was the Bruininks-Oseretsky protocol, praxis tests fine (oculomotor). we selected 70 children (35 of each sex), aged between 10 and 13 years. All of the same public high school that offers physical education. students selected physically inactive targeted outside the school environment. Students selected physically inactive targeted outside the school environment. From these peculiarities is intended to call into question the interference in the development of fine motor skills of praxis in children who have access to physical education. The results were that no significant differences between genders for the sub-test A and B sub-test, considering boys score better. However for the sub-test C, both had the same score. In sub-test D, the difference was not significant between genders, whereas the girls with a higher ranking among the points. Considering the high average age and experience in preschool, the score obtained in this study was significantly lower in both genders.
Keywords: Fine motor coordination; Elementary school students; Motor assessmen